A Retrospective Study of Conservative Treatment of Gastric Dilatation-Volvulus in the Dog - Eggertsdóttir, A. V. (Acta Vet Scand, 1995)
A retrospective study of 103 dogs with gastric dilatation-volvulus (GDV) treated conservatively during the period 1985–1989 was performed. The date and number of recurrences, and the date and cause of death along with breed, age and sex were collected from clinic records and from a questionnaire sent to the owners (77% response). The treatment consisted of emptying the stomach with a stomach tube, gastrocentesis if necessary and treating shock. All of the affected dogs were from moderate to large sized breeds and the study showed that particular breeds appear to be predisposed to GDV. The average age was 7.2 years and there was no gender predisposition. Sixty-six per cent of the dogs survived the initial treatment and 50% of the dogs were still alive 1 month after treatment. Thirty-nine dogs (71%) received recurrence between 5–760 days after initial treatment. Fifty-six per cent had recurrence within 3 months and all except 2 dogs, within 1 year. Data for the time of death, regardless of cause, was available for 68 dogs. Of these 59 (81% ) died within a year after initial treatment. Conservative treatment was found to be an adequate life-saving procedure in the acute stage of GDV, but could not alone prevent recurrence of the disease.